Electrode for all-solid-state battery
The electrode for all-solid-state batteries, featuring granules coated with a sulfide-based solid electrolyte and optimized with carbon black and a binder, addresses the challenges of porosity and moisture sensitivity, enhancing electrical conductivity and battery performance.
Patent Information
- Application Number
- JP2024559053
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-08-29
AI Technical Summary
Existing all-solid-state batteries face challenges with the aggregation of active materials and solid electrolytes, leading to porosity issues and reduced performance, particularly when using sulfide-based solid electrolytes which are sensitive to moisture.
The development of an electrode for all-solid-state batteries comprising granules coated with a sulfide-based solid electrolyte, where the granules contain an active material, a conductive material (carbon black with specific particle size and distribution), and a binder, optimized to improve electrical conductivity and battery performance.
The proposed electrode design enhances the electrical conductivity of the granules and improves the overall performance of the all-solid-state battery by optimizing the distribution and content of the conductive material, thereby addressing the porosity and moisture sensitivity issues.
Smart Images

Figure 2025511679000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to an electrode for an all-solid-state battery, in particular to a positive electrode for an all-solid-state battery comprising granules coated with a sulfide-based solid electrolyte.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0110540 dated September 1, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]
[0003] Currently, various batteries capable of overcoming the limitations of lithium secondary batteries are being researched from the standpoints of battery capacity, safety, output, large size, and ultra-compactness.
[0004] Representative examples include metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and have no risk of explosion, supercapacitors, NaS batteries or RFBs (redox flow batteries), and thin film batteries, which are being continuously researched in both academia and industry.
[0005] Among these, all-solid-state batteries refer to batteries in which the liquid electrolyte used in conventional lithium secondary batteries is replaced with a solid, and since they do not use flammable solvents in the battery, there is absolutely no risk of fire or explosion due to the decomposition reaction of conventional electrolytes, which greatly improves safety. In addition, because Li metal or Li alloys can be used as the anode material, there is the advantage that the energy density relative to the mass and volume of the battery can be dramatically improved.
[0006] In particular, inorganic solid electrolytes among solid electrolytes in solid-state batteries are divided into sulfide-based and oxide-based. Currently, the solid electrolyte that has seen the most technological development is the sulfide-based solid electrolyte, and materials have been developed that have an ionic conductivity close to that of organic electrolytes.
[0007] Sulfide-based solid electrolytes are 10% of all solid electrolytes. -3 ~10 -2 It has a high ionic conductivity of S / cm, is ductile, and has good contact with the interface, which is advantageous for improving resistance, but it is sensitive to moisture, e.g., it generates H2S gas when it comes into contact with water, so it is necessary to create an extremely dry environment during production. In addition, it is necessary to improve the cohesion of the active material and solid electrolyte, and a high-density electrode is required by reducing the porosity.
[0008] Therefore, in order to solve the problems faced in the technical field, the present inventors have continuously studied electrodes for all-solid-state batteries and completed the present invention. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 10-2016-0146737 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention provides an electrode for an all-solid-state battery that includes granules coated with a sulfide-based solid electrolyte, and that can improve the performance of the battery when used as an electrode for an all-solid-state battery. [Means for solving the problem]
[0011] According to a first aspect of the present invention, The present invention provides an electrode for an all-solid-state battery including granules coated with a sulfide-based solid electrolyte, the granules including an active material, a conductive material, and a binder, and the conductive material is carbon black having an average particle size of 120 nm to 200 nm.
[0012] In one embodiment of the present invention, the carbon black is 2 / g~35m 2 / g BET specific surface area.
[0013] In one embodiment of the present invention, the carbon black has a DBP absorption rate of 70 ml / 100 g to 100 ml / 100 g.
[0014] In one embodiment of the present invention, the carbon black aggregates to form secondary particles, and the secondary particles have a particle size of 600 nm to 1,100 nm.
[0015] In one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 150 μm.
[0016] In one embodiment of the present invention, the electrode for an all-solid-state battery is characterized in that the granules have a porosity of 20% to 40%.
[0017] In one embodiment of the present invention, the electrode for an all-solid-state battery is a positive electrode, and the active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2(0 <a<1,0<b<1,0<c<1,a+b+c=1)、LiNi 1-y Co y O2(0 <y<1)、LiCo 1-y Mn y O2(0 <y<1)、LiNi 1-y Mn y O2(0 <y<1)、Li(Ni a Co b Mn c)O4(0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4(0 < z < 2), LiMn 2-z Co z O4(0 < z < 2) and is selected from the group consisting of combinations thereof.
[0018] In one embodiment of the present invention, the binder is an organic binder, and the organic binder is selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride - hexafluoropropylene copolymer (PVDF - co - HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene - propylene - diene monomer (EPDM), sulfonated EPDM, styrene - butadiene rubber, and fluororubber.
[0019] In one embodiment of the present invention, the granules contain 85 wt% - 99.8 wt% of active material, 0.1 wt% - 10 wt% of binder, and 0.1 wt% - 10 wt% of conductive material.
[0020] In one embodiment of the present invention, in the electrode for all - solid - state battery, the electrode active material layer containing granules coated with a sulfide - based solid electrolyte has a thickness of 100 μm - 300 μm.
[0021] In one embodiment of the present invention, in the electrode for all - solid - state battery, the electrode active material layer containing granules coated with a sulfide - based solid electrolyte contains 10 wt% - 30 wt% of sulfide - based solid electrolyte based on the content of the granules.
[0022] In one embodiment of the present invention, when the granules are divided at the same interval according to the inner diameter of the granules and separated into a first region, a second region, and a third region in order from the center of the granules to the outside of the granules, the content of the conductive material in the granules increases in the order of the first region, the second region, and the third region.
[0023] In one embodiment of the present invention, the granules have an R value of 5 or less, the R value being defined by the following mathematical formula 1:
[0024] According to a second aspect of the present invention, The present invention provides an all-solid-state battery including the above-mentioned all-solid-state battery electrode as a positive electrode or a negative electrode. Effect of the Invention
[0025] In an electrode for an all-solid-state battery including granules coated with a sulfide-based solid electrolyte, the granules include an active material, a conductive material, and a binder. By specifying the physical properties of the primary or secondary particles of carbon black, which is the conductive material contained in the granules, not only can the electrical conductivity of the granules be improved, but also the performance of a battery to which the granules are applied can be improved. [Brief description of the drawings]
[0026] [Figure 1a] 1 is an SEM image (magnification x1,000) of granules of Production Example 1 in Experimental Example 1. [Figure 1b] 1 is an SEM image (magnification x5,000) of granules of Production Example 1 in Experimental Example 1. [Figure 2a] 1 is an SEM image (magnification x1,000) of granules of Comparative Production Example 1 in Experimental Example 1. [Figure 2b] 1 is an SEM image (magnification x 5,000) of granules of Comparative Production Example 1 in Experimental Example 1. [Diagram 3] FIG. 2 is a diagram showing the positions of a first region (A), a second region (B) and a third region (C) in a granule. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The embodiments provided in accordance with the present invention can all be achieved by the following description. The following description should be understood as describing preferred embodiments of the present invention, and it should be understood that the present invention is not necessarily limited thereto.
[0028] Unless the measurement conditions and methods are specifically described for the physical properties described in this specification, the physical properties are measured according to the measurement conditions and methods commonly used by those of ordinary skill in the art.
[0029] In one aspect of the present invention, an electrode for an all-solid-state battery is provided, which includes granules coated with a sulfide-based solid electrolyte. The granules are spherical particles including an active material, a conductive material, and a binder. Here, the term "spherical" does not mean a perfect sphere in the strict sense, but is generally used as a comprehensive concept including round particles. The active material in the form of a powder is bound to the conductive material in the form of primary particles or secondary particles by a binder solution, and grows into particles having a specific range of specifications. The conductive material may be applied as primary particles, secondary particles, or a mixture of primary particles and secondary particles.
[0030] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 150 μm. Here, the spherical particles do not mean perfectly spherical particles, so the diameter means the largest value among the distances from any one point on the particle surface to another point on the surface. Specifically, the diameter of the granules is 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, and 150 μm or less, 145 μm or less, 140 μm or less, 135 μm or less, 130 μm or less, 125 μm or less, 120 μm or less, and may be 30 μm to 150 μm, 40 μm to 140 μm, or 50 μm to 120 μm. If the diameter of the granules is less than the above range, the voids in the granule layer are small, and the amount of the sulfide-based solid electrolyte that penetrates between the granules and coats them is reduced, so that the improvement in battery performance may not be significant. If the diameter of the granules is more than the above range, the distance between the surface in contact with the sulfide-based solid electrolyte and the center of the granule becomes large, so that the improvement in battery performance may not be significant.
[0031] The electrode for an all-solid-state battery according to one embodiment of the present invention may be either a negative electrode or a positive electrode, and more specifically, the electrode for an all-solid-state battery may be a positive electrode.
[0032] When the electrode is a negative electrode, the electrode active material contained in the granule may be any material that can be used as the negative electrode active material of a lithium ion secondary battery. For example, the negative electrode active material may be carbon such as graphitizable carbon or graphite-based carbon; Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Group 1, Group 2, Group 3 of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides and the like may be used. According to one embodiment of the present invention, the negative electrode active material may contain a carbon-based material and / or Si.
[0033] When the electrode is a positive electrode, the electrode active material contained in the granule may be used without limitation as long as it can be used as the positive electrode active material of a lithium ion secondary battery. For example, the positive electrode active material may be a lithium transition metal oxide containing one or more transition metals. In one embodiment of the present invention, the positive electrode active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-y Co y O2 (0 < y < 1), LiCo 1-y Mn y O2 (0 < y < 1), LiNi 1-y Mn y O2 (0 < y < 1), Li(Ni a Cob Mn c )O4(0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4(0 < z < 2), LiMn 2-z Co z O4(0 < z < 2) and is selected from the group consisting of combinations thereof.
[0034] The conductive material contained in the particles according to one embodiment of the present invention is carbon black having an average particle diameter of 120 nm to 200 nm. Here, the average particle diameter is the arithmetic average value of the particle diameters. Specifically, the average particle diameter of the carbon black is 120 nm or more, 125 nm or more, 130 nm or more, 135 nm or more, and 200 nm or less, 190 nm or less, 180 nm or less, 170 nm or less, and may be 120 nm to 200 nm, 130 nm to 190 nm, 135 nm to 170 nm. When the diameter of the carbon black is less than the above range, the external area of the carbon black is small, and it is difficult for the conductive material to form a structure effective for exerting functionality among a large number of active material particles. When the diameter of the carbon black exceeds the above range, it is difficult for the conductive material to be dispersed and positioned at an appropriate position. Further, the conductive material having a particle diameter within the above-described range helps to form secondary particles having preferable physical properties.
[0035] According to one embodiment of the present invention, the carbon black is 15 m 2 / g to 35 m 2 / g has a BET specific surface area. The BET specific surface area is the specific surface area measured by the BET method. Specifically, the BET specific surface area of the carbon black is 15 m 2 / g or more, 16 m 2 / g or more, 17 m 2 / g or more, 18 m 2 / g or more, 19 m 2 / g or more, 20 m 2 / g or more, and 35 m 2 / g or less, 34 m 2 / g or less, 33 m 2 / g or less, 32 m 2 / g or less, 31 m 2 / g or less, 30 m2 / g or less, 15m 2 / g~35m 2 / g, 17m 2 / g~33m 2 / g, 20m 2 / g~30m 2 / g. If the BET specific surface area of the carbon black is less than the above range, the area of contact with the active material relative to the weight of the carbon black is reduced, making it difficult to ensure functionality, whereas if the BET specific surface area of the carbon black exceeds the above range, the carbon black does not come into contact with the active material or solid electrolyte as easily as the specific surface area exceeds the above range, making it difficult to ensure functionality. In addition, a conductive material having a particle size within the above range is useful for forming secondary particles with desirable physical properties.
[0036] According to one embodiment of the present invention, the carbon black as the conductive material is aggregated to form secondary particles, and the secondary particles have a particle size of 600 nm to 1,100 nm. In this specification, the carbon black before being aggregated into secondary particles can be expressed as a primary particle. The secondary particles may be aggregated in various forms during aggregation, and the particle size means the largest value among the distances from any one point on the particle surface to another surface point. When carbon black is aggregated and used in the form of secondary particles, the conductive network between each carbon black constituting the secondary particles is maintained, and electrolytes and active materials can be accessed through the voids between the carbon black, so that a highly functional structure can be formed. Specifically, the particle size of the secondary particles may be 600 nm or more, 650 nm or more, 700 nm or more, 1,100 nm or less, 1,000 nm or less, 900 nm or less, or 600 nm to 1,100 nm, 650 nm to 1,000 nm, or 700 nm to 900 nm. If the particle size of the secondary particles is less than the above range, the functionality obtained by forming the secondary particles may be negligible, and if the particle size of the secondary particles is more than the above range, the conductive material may be excessively agglomerated and located, making it difficult to efficiently disperse the conductive material throughout the granules.
[0037] According to one embodiment of the present invention, the carbon black as the conductive material has a DBP absorption rate of 70ml / 100g to 100ml / 100g. The DBP absorption rate is measured by mixing DBP (dibutyl phthalate) as a plasticizer and measuring the change in torque caused by impregnation with the plasticizer, and the DBP absorption rate of the conductive material can affect the formation of secondary particles by the conductive material. Specifically, the DBP absorptivity of the carbon black is 70 ml / 100 g or more, 71 ml / 100 g or more, 72 ml / 100 g or more, 73 ml / 100 g or more, 74 ml / 100 g or more, 75 ml / 100 g or more, and 100 ml / 100 g or less, 98 ml / 100 g or less, 96 ml / 100 g or less, 94 ml / 100 g or less, 92 ml / 100 g or less, 90 ml / 100 g or less, or 70 ml / 100 g to 100 ml / 100 g, 73 ml / 100 g to 94 ml / 100 g, or 75 ml / 100 g to 90 ml / 100 g. Carbon black having a DBP absorptivity within the above range is useful for forming secondary particles with preferred physical properties.
[0038] The binder contained in the granules according to one embodiment of the present invention is mixed with the active material, which is a fine powder particle, and the conductive material, which is a primary or secondary particle, to bind the components together and aid in particle growth. Since the sulfide-based solid electrolyte is sensitive to moisture, e.g., it generates H2S gas when it comes into contact with moisture, it is preferable to remove moisture as much as possible from the time of forming the granules. According to one embodiment of the present invention, the binder is an organic binder. The organic binder refers to a binder that dissolves or disperses in an organic solvent, particularly N-methylpyrrolidone (NMP), and is distinguished from an aqueous binder that uses water as a solvent or dispersion medium. Specifically, the organic binder may be selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber, but is not limited thereto.
[0039] According to one embodiment of the present invention, the granules contain 85% to 99.8% by weight of active material, specifically 88% to 99.5% by weight, more specifically 90% to 99.3% by weight of binder, 0.1% to 10% by weight, specifically 0.2% to 8% by weight, more specifically 0.3% to 7% by weight of conductive material, and 0.1% to 10% by weight, specifically 0.15% to 8% by weight, more specifically 0.2% to 5% by weight of conductive material. The content of active material, binder, and conductive material is adjusted within the above-mentioned ranges, which is advantageous for improving the performance of the battery.
[0040] According to one embodiment of the present invention, the granules have a porosity of 20% to 40%. The porosity of the granules means the volume ratio of the voids in the granules. Specifically, the porosity of the granules may be 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 40% or less, 39% or less, 38% or less, 37% or less, 36% or less, or 35% or less. If the porosity of the granules is less than the above range, the sulfide-based solid electrolyte is unlikely to come into close contact with the granules, and the improvement in battery performance may not be significant. If the porosity of the granules is more than the above range, the amount of active material is reduced compared to the volume of the granules, and it is difficult to provide an electrode with a high loading of active material, and the improvement in battery performance may not be significant.
[0041] In general, when manufacturing granules, a binder solution is added together with fine powdered active material and conductive material to grow the particle size of the granules to a certain level, and at this time, the inside of the device may rotate to make the granules spherical and separate each granule. This rotation causes centrifugal force to act on the granules, and the components of the granules may be present more densely on the outside of the granules than in the center of the granules. However, when manufacturing granules according to an embodiment of the present invention, the conductive material can be uniformly distributed within the granules by minimizing the movement of the conductive material toward the surface of the granules during the high-temperature solvent drying process. This can be confirmed through SEM images of Figures 1 and 2 in Experimental Example 1 below. If the conductive material moves significantly toward the surface of the granules as shown in Figure 2, not only the porosity of the granules decreases, but the active material in the granules is not easily exposed to the electrolyte, which may result in a decrease in battery performance.
[0042] 3 is a diagram showing a schematic shape of a granule according to an embodiment of the present invention, and as shown in FIG. 3, the inside of the granule can be separated into a first region (region A), a second region (region B), and a third region (region C). The first region, the second region, and the third region are separated at equal intervals on the inside diameter of the granule, with the first region being located at the most central portion of the granule, the third region being located at the most outer portion of the granule, and the second region being located between the first region and the third region. According to an embodiment of the present invention, the conductive material content in the granule increases in the order of the first region, the second region, and the third region.
[0043] According to one embodiment of the present invention, the granule has an R value of 5 or less, 4.5 or less, or 4 or less. Here, the R value is a numerical representation of the change in conductive material content between adjacent regions, and is defined by the following Equation 1:
[0044] [Formula 1]
number
[0045] where r A is the content (%) of the conductive material in the first region, and r B is the content (%) of conductive material in the second region, and r C is the conductive material content (%) in the third region. The conductive material content in each region is based on the total conductive material content of the granules, so r A , r B , r C The sum of these is 100%. Basically, the content of the conductive material according to one embodiment of the present invention increases in the order of the first region, the second region, and the third region, so that the R value has a value of 1 or more. If the difference in the conductive material content between each region is large, the R value may be high, and if the difference in the conductive material content between each region is small, the R value may be low. If the R value is low, the conductive material is distributed uniformly, which may help improve the electrical conductivity of the entire granule, but the electrical conductivity of the granule is affected not only by the R value, but also by the size, shape, content, etc. of the conductive material.
[0046] In the all-solid-state electrode, the solid electrolyte is coated on at least a part or the whole of the surface of the granule. The solid electrolyte may be a polymer solid electrolyte formed by adding a polymer resin to a solvated lithium salt, or a polymer gel electrolyte in which an organic electrolyte containing an organic solvent and a lithium salt, an ionic liquid, a monomer or an oligomer, etc., is contained in a polymer resin. The solid electrolyte may be one or more selected from a polymer solid electrolyte, a sulfide solid electrolyte, and an oxide solid electrolyte, and according to one embodiment of the present invention, the solid electrolyte is a sulfide solid electrolyte. In the all-solid-state electrode, the sulfide solid electrolyte is applied by impregnating a granule layer made of the granules described above into the sulfide electrolyte and then drying.
[0047] According to one embodiment of the present invention, the lithium salt is an ionizable lithium salt, Li + X - The anion of such a lithium salt is not particularly limited, but may be represented by F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 -, SCN - , (CF3CF2SO2)2N - In one embodiment of the present invention, the sulfide-based solid electrolyte contains sulfur (S) and has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS-based glass or Li-PS-based glass ceramic. Non-limiting examples of these sulfide-based solid electrolytes include, and may include one or more of, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-LiCl-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, and the like.
[0048] The electrode for an all-solid-state battery according to an embodiment of the present invention may be prepared by loading granules onto a current collector to prepare a sheet-shaped granular layer, impregnating the granular layer with a sulfide-based electrolyte, and drying the same. In this case, the current collector is an electrically conductive material such as a metal plate, and an electrode known in the art may be appropriately used according to the polarity of the battery.
[0049] According to one embodiment of the present invention, in the electrode for an all-solid-state battery, the electrode active material layer containing granules coated with a sulfide-based solid electrolyte has a thickness of 100 μm to 300 μm. Here, the electrode active material layer means a sheet-like layer applied on a current collector, excluding the current collector, when a current collector is used in the manufacture of the electrode. Specifically, the thickness of the electrode active material layer may be 100 μm or more, 110 μm or more, 120 μm or more, 130 μm or more, 140 μm or more, 150 μm or more, or 300 μm or less, 290 μm or less, 280 μm or less, 270 μm or less, 260 μm or less, or 250 μm or less. If the thickness of the electrode active material layer is less than the above range, the loading amount of the active material may decrease, and the improvement in the performance of the battery may not be noticeable, and if the thickness of the electrode active material layer exceeds the above range, the durability of the electrode may decrease, and the improvement in the performance of the battery may not be noticeable.
[0050] According to one embodiment of the present invention, in the electrode for the all-solid-state battery, the electrode active material layer including the granules coated with the sulfide-based solid electrolyte includes 10 wt% to 30 wt% of the sulfide-based solid electrolyte based on the content of the granules. Specifically, the content of the sulfide-based solid electrolyte may be 10 wt% or more, 11 wt% or more, 12 wt% or more, 13 wt% or more, 14 wt% or more, or 15 wt% or more, or 30 wt% or less, 29 wt% or less, 28 wt% or less, 27 wt% or less, 26 wt% or less, or 25 wt% or less. If the content of the sulfide-based solid electrolyte is less than the above range, the electron transfer between the electrolyte and the active material in the all-solid-state battery may not be easy, and the improvement in the performance of the battery may not be noticeable. If the content of the sulfide-based solid electrolyte is more than the above range, the loading amount of the active material may be relatively reduced, and the improvement in the performance of the battery may not be noticeable.
[0051] In one aspect of the present invention, an all-solid-state battery is provided that includes the above-mentioned all-solid-state battery electrode as a positive electrode and / or a negative electrode. In constructing the all-solid-state battery, in addition to the solid electrolyte contained in the electrode, a separate solid electrolyte layer may be introduced between the positive electrode and the negative electrode, and such a solid electrolyte layer may also function as a separator in a general lithium secondary battery. The above-mentioned electrode may be used together with a liquid electrolyte as a semi-solid-state battery, in which case a separate polymer separator may be further required.
[0052] The polymer separator is interposed between the negative electrode and the positive electrode, and serves to electrically insulate the negative electrode from the positive electrode while allowing lithium ions to pass through. The polymer separator may be any polymer separator membrane used in the field of general all-solid-state batteries, and is not particularly limited.
[0053] In one aspect of the present invention, there is provided a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0054] Specific examples of the device include, but are not limited to, power tools that are powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0055] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to make the present invention easier to understand, and the present invention is not limited to these examples.
[0056] Manufacturing example: Manufacturing granules containing active materials Manufacturing Example 1 LiNi as active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon black (average particle size (D 50 ): approx. 150nm, BET specific surface area: approx. 25m 2 The secondary particles (particle size: about 800 nm) were agglomerated from the active material (active material / g, DBP absorption rate: about 81 ml / 100 g) and polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 94:3:3 (active material: conductive material: binder) in N-methylpyrrolidone solvent to produce a slurry, which was then spray-dried to produce granules with a diameter of about 60 μm (porosity: 31%).
[0057] Comparative Manufacturing Example 1 LiNi as active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon black (average particle size (D 50 ): approx. 30nm, BET specific surface area: approx. 120m 2 The secondary particles (particle size: about 150 nm) were agglomerated from the active material (active material: conductive material: binder) and polyvinylidene fluoride (PVDF) was mixed in a weight ratio of 94:3:3 (active material: conductive material: binder) in N-methylpyrrolidone solvent to produce a slurry, which was then spray-dried to produce granules with a diameter of about 60 μm (porosity: 15%).
[0058] Comparative Manufacturing Example 2 LiNi as active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon black (average particle size (D 50 ): approx. 40nm, BET specific surface area: approx. 90m 2The secondary particles (particle size: about 750 nm) were agglomerated from the active material (active material: conductive material: binder) and polyvinylidene fluoride (PVDF) was mixed in a weight ratio of 94:3:3 (active material: conductive material: binder) in N-methylpyrrolidone solvent to produce a slurry, which was then spray-dried to produce granules with a diameter of about 60 μm (porosity: 19%).
[0059] Comparative Manufacturing Example 3 LiNi as active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon black (average particle size (D 50 ): approx. 280nm, BET specific surface area: approx. 9m 2 The secondary particles (particle size: about 3,000 nm) were agglomerated from the active material (active material: conductive material: binder) and polyvinylidene fluoride (PVDF) was mixed in a weight ratio of 94:3:3 (active material: conductive material: binder) in N-methylpyrrolidone solvent to produce a slurry, which was then spray-dried to produce granules with a diameter of about 60 μm (porosity: 37%).
[0060] The physical properties of the granules produced in Production Example 1 and Comparative Production Examples 1 to 3 are summarized in Table 1 below.
[0061] [Table 1]
[0062] 1) Average particle size of conductive primary particles (nm): After measuring each particle size distinguished in a SEM (Scanning Electron Microscope) image, the arithmetic average value of the measured values was calculated.
[0063] 2) BET specific surface area of the conductive material primary particles (m 2 / g): Calculated from the mass gas adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mino II manufactured by BEL Japan.
[0064] 3) DBP absorption rate of primary particles of conductive material (ml / 100g): Using an oil absorption measuring device (Asahi's S-500), the plasticizer DBP (dibutyl phthalate) was mixed with the conductive material, and the change in torque generated by the plasticizer impregnation was measured. The oil absorption amount at which the viscosity, expressed as a torque value, reached its maximum value was calculated as the DBP adsorption value.
[0065] 4) Particle size of secondary particles of conductive material (nm): Measured by a wet method using a particle size analyzer (Malvern's Mastersizer).
[0066] 5) Granule porosity (%): Measured using a mercury porosity analyzer (Autopore, Micromeritics).
[0067] 6) Conductive material content (%) of the first, second or third region of the granule: The content ratio of the conductive material in a specific region to the total conductive material in the cross section of the granule was calculated using SEM, EDS (Energy Dispersive Spectroscopy) measurement and an image analysis program.
[0068] 7) R value of granular conductive material: Calculated using the above formula 1 based on the result value of 6) above.
[0069] 8) Electrical conductivity of granules (%): Measured using a 4-Probe powder electrical conductivity measuring electrode (Mitsubishi Chemical's powder resistance system (MCP-PD51)) and calculated as a percentage based on Preparation Example 1.
[0070] Example: Manufacture of electrodes and batteries containing the produced granules Example 1 The granules prepared in Preparation Example 1 were applied to one side of an aluminum current collector, rolled, impregnated with a sulfide-based electrolyte of Li2S-P2S5, dried and rolled to prepare a positive electrode with a thickness of about 130 μm (the sulfide-based electrolyte was about 20% by weight of the granules). Li2S-LiCl-P2S5 was mixed with a polyvinylidene fluoride (PVDF) solution (a solution in which PVDF and toluene were mixed in a weight ratio of 8:92) to prepare a slurry, which was then applied to a thickness of about 100 μm on a lithium foil (Li foil) with a thickness of about 50 μm to prepare a solid electrolyte and a negative electrode including the same. The positive and negative electrodes were stacked and pressed to prepare an electrode assembly, which was then placed inside a battery case to prepare an all-solid-state battery.
[0071] Comparative Example 1 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 1 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0072] Comparative Example 2 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 2 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0073] Comparative Example 3 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 3 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0074] Experimental Example: Evaluation of Manufacturing Examples and Working Examples Experimental example 1: SEM image of granules SEM images of the granules prepared in Preparation Example 1 and Comparative Preparation Example 1 were taken and are shown in Figure 1 (Preparation Example 1) and Figure 2 (Comparative Preparation Example 1). Specifically, in Figures 1a and 2a, the overall shape of the granules was observed at a magnification of 1,000x, and in Figures 1b and 2b, the distribution of the conductive material on the surface of the active material of the granules was observed at a magnification of 5,000x.
[0075] 1a and 1b, the conductive material was distributed on the surface of the active material in the form of clear particles, and the active material particles were clearly distinguished from the granules, whereas, according to Fig. 2a and 2b, at that magnification, the conductive material had very fine particles, covering the active material particles to the extent that the active material surface was not visible, and the boundary between the granules and the active material particles was unclear.
[0076] Experimental example 2: Battery performance evaluation The batteries of Example 1 and Comparative Examples 1 to 3 were discharged at 0.1 C and 1.0 C, respectively, and the discharge capacity ratio (1.0 C discharge capacity / 0.1 C discharge capacity×100, %) was measured. The results are shown in Table 2 below.
[0077] [Table 2]
[0078] As shown in Tables 1 and 2, the granules of Preparation Example 1 had higher electrical conductivity than the granules of Comparative Preparation Examples 1 to 3. In addition, the battery of Example 1 including an electrode manufactured using the granules of Preparation Example 1 did not show a significant decrease in battery performance even under higher C-rate conditions compared to the batteries of Comparative Examples 1 to 3 including electrodes manufactured using the granules of Comparative Preparation Examples 1 to 3.
[0079] All mere variations and modifications of the present invention belong to the scope of the present invention, and the specific scope of protection of the present invention will be apparent from the appended claims.
Claims
1. An electrode for an all-solid-state battery comprising granules coated with a sulfide-based solid electrolyte, The granules include an active material, a conductive material, and a binder, The conductive material is carbon black having an average particle size of 120 nm to 200 nm.
2. The carbon black is 15 m 2 / g to 35m 2 The electrode for an all-solid-state battery according to claim 1 , characterized in that it has a BET specific surface area of 100 nm / g.
3. The electrode for an all-solid-state battery according to claim 1, wherein the carbon black has a DBP absorption rate of 70 ml / 100 g to 100 ml / 100 g.
4. The carbon black aggregates to form secondary particles, The electrode for an all-solid-state battery according to claim 1, wherein the secondary particles have a particle size of 600 nm to 1,100 nm.
5. The electrode for an all-solid-state battery according to claim 1, wherein the granules are spherical particles having a diameter of 30 μm to 150 μm.
6. The electrode for an all-solid-state battery according to claim 1, wherein the granules have a porosity of 20% to 40%.
7. The electrode for an all-solid-state battery is a positive electrode, The active material is LiCoO 2 , LiNiO 2 , LiMnO 2 , Li 2 MnO 3 , LiMn 2 O 4 , Li(Ni a Co b Mn c ) O 2 (0<a<1, 0<b<1, 0<c<1, a+b+c=1), LiNi 1-y Co y O 2 (0<y<1), LiCo 1-y Mn y O 2 (0<y<1), LiNi 1-y Mn y O 2 (0<y<1), Li(Ni a Co b Mn c ) O 4 (0<a<2, 0<b<2, 0<c<2, a+b+c=2), LiMn 2-z Ni z O 4 (0<z<2), LiMn 2-z Co z O 4 The electrode for an all-solid-state battery according to claim 1 , wherein z is selected from the group consisting of (0<z<2) and combinations thereof.
8. The binder is an organic binder, 2. The electrode for an all-solid-state battery according to claim 1, wherein the organic binder is selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber.
9. The electrode for an all-solid-state battery according to claim 1, wherein the granules contain 85% by weight to 99.8% by weight of an active material, 0.1% by weight to 10% by weight of a binder, and 0.1% by weight to 10% by weight of a conductive material.
10. 2. The electrode for an all-solid-state battery according to claim 1, wherein the electrode active material layer including the granules coated with the sulfide-based solid electrolyte has a thickness of 100 μm to 300 μm.
11. 2. The electrode for an all-solid-state battery according to claim 1, wherein the electrode active material layer including the granules coated with the sulfide-based solid electrolyte contains 10 wt % to 30 wt % of the sulfide-based solid electrolyte based on a content of the granules.
12. 2. The electrode for an all-solid-state battery according to claim 1, wherein when the inner diameter of the granule is divided into a first region, a second region, and a third region in the order from a center of the granule to an outer periphery of the granule at equal intervals, the conductive material content in the granule increases in the order of the first region, the second region, and the third region.
13. The electrode for an all-solid-state battery according to claim 12, wherein the granules have an R value of 5 or less, and the R value is defined by the following Equation 1: [Formula 1] [0010] Here, r A is the content (%) of the conductive material in the first region, and r B is the content (%) of the conductive material in the second region, and r C is the content (%) of the conductive material in the third region, and the content of the conductive material in each region is based on the total conductive material content of the granule.
14. An all-solid-state battery comprising the electrode for an all-solid-state battery according to claim 1 as a positive electrode or a negative electrode.
Citation Information
Patent Citations
Method for manufacturing positive electrode mixture layer for nonaqueous electrolyte secondary battery
JP2016154097A
Electrode composition, electrode for lithium secondary battery, method of manufacturing the electrode and lithium secondary battery including the electrode
US20110281166A1
All-solid secondary battery electrode composite particles, method of manufacturing same, all-solid secondary battery electrode, and all-solid secondary battery
WO2019065030A1
Production method for complex particles for use in electrode of electrochemical element
KR1020160146737A